2003
DOI: 10.1016/s0261-5614(03)80229-7
|View full text |Cite
|
Sign up to set email alerts
|

The agreement between measured and predicted resting energy expenditure in patients with pancreatic cancer — A pilot study

Abstract: Objective To compare measured resting energy expenditure to resting energy expenditure predicted from eight published prediction equations in a sample of patients with pancreatic cancer.Design Cross-sectional study.Setting Ambulatory patients of a tertiary private hospital.Participants Eight patients with pancreatic cancer (5 males, 3 females; age: 62.0±5.2 years; BMI: 24.4±3.2 kg/m 2 ; weight loss: 12.1±6.0%; mean±SD). MethodsResting energy expenditure was measured using indirect calorimetry and predicted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…It is also the most accurate in older individuals (≥ 70 years old) (36). In a pilot study similar to our own, Bauer et al (5) found in pancreatic cancer patients Mifflin-St Jeor had the greatest underestimation, but was still accurate at the group level. The differences in our conclusions and those of Bauer et al (5) could be related to the narrower age range (55-70 years), the current weight status of their patients (currently normal weight or overweight with a weight loss of ≥5% in the last six months), or the repeated observations on four participants.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…It is also the most accurate in older individuals (≥ 70 years old) (36). In a pilot study similar to our own, Bauer et al (5) found in pancreatic cancer patients Mifflin-St Jeor had the greatest underestimation, but was still accurate at the group level. The differences in our conclusions and those of Bauer et al (5) could be related to the narrower age range (55-70 years), the current weight status of their patients (currently normal weight or overweight with a weight loss of ≥5% in the last six months), or the repeated observations on four participants.…”
Section: Discussionsupporting
confidence: 77%
“…If the mean difference was close to zero and not statistically significant, we would conclude that cREE is a reasonably accurate representation of mREE. The Bland-Altman approach (5, 28) was used to assess the agreement between mREE and each cREE. This method calculates bias, which is defined as the mean of the differences between the predicted and measured REE, and the limits of agreement, which are defined as ± 2 standard deviations from the mean difference.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Empiric formulas to predict energy expenditure from body weight, body surface and body height have been developed for humans (e.g. Bauer et al, 2004;Cunningham, 1991;Kien and Ugrasbul, 2004;Schofield, 1985). However, these approaches are only adequate to predict mean values for particular populations of humans or animals.…”
Section: Introductionmentioning
confidence: 99%